EMOTIONS IN THE SYSTEM OF THINKING ACTIVITY - L.V. Beshevets (Academy of Cognitive and Natural Sciences, 2009)
The article deals with different aspects of intellectual activities from the viewpoint of A. Leontiev's psychological theory of activities. The main point of "unity of an affect and an intellect" problem is revealed.